2018
DOI: 10.1155/2018/5848046
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges and Opportunities in the Clinical Application of Noncoding RNAs: The Road Map for miRNAs and piRNAs in Cancer Diagnostics and Prognostics

Abstract: Discoveries on nonprotein-coding RNAs have induced a paradigm shift in our overall understanding of gene expression and regulation. We now understand that coding and noncoding RNA machinery work in concert to maintain overall homeostasis. Based on their length, noncoding RNAs are broadly classified into two groups—long (>200 nt) and small noncoding RNAs (<200 nt). These RNAs perform diverse functions—gene regulation, splicing, translation, and posttranscriptional modifications. MicroRNAs (miRNAs) and PIWI-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 189 publications
(215 reference statements)
0
35
0
1
Order By: Relevance
“…This enormous enthusiasm in miRNA investigation was not replicated to the same extent in the investigation of other ncRNAs. Some studies focused on the analysis of lncRNAs as biomarkers, while recent studies revealed new functions and implication of piRNAs in oncogenesis [457]. To date, the scientific community is trying to decipher and understand the complex pathways and interactions by which ncRNAs are implicated in oncogenesis.…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This enormous enthusiasm in miRNA investigation was not replicated to the same extent in the investigation of other ncRNAs. Some studies focused on the analysis of lncRNAs as biomarkers, while recent studies revealed new functions and implication of piRNAs in oncogenesis [457]. To date, the scientific community is trying to decipher and understand the complex pathways and interactions by which ncRNAs are implicated in oncogenesis.…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…With the development of NGS techniques, many researchers have embarked on genome/transcriptome sequencing from a wide set of samples. Due to this specific technology, new species of previously not described ncRNAs have been reported, including for example piRNAs, which have been discovered just in 2006 [457]. The advancements in this field may conduct to the discovery of new, more specific and sensitive molecules to be used as biomarkers and give new insights into the so-called “junk” DNA/RNA.…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…Small Noncoding RNA Expression in Cancer DOI: http://dx.doi.org/10.5772/intechopen.84270 piRNA functions described in germ cells, there is increasing evidence of multifaceted action not restricted to transposon silencing in somatic cells [70]. Although the function of piRNAs in somatic cells and their relationship with tumorigenesis and cancer progression are still unknown, many studies seek to evaluate PIWI proteins and piRNA expression in a variety of malignancies [71].…”
Section: Pipeline For Detection and Characterization Of Known And Novmentioning
confidence: 99%
“…However, more recent evidence has shown their biological and clinical potential as emerging studies demonstrate that aberrant expression of piRNAs is a unique characteristic in several diseases, including cancers 1517. It has been found that piRNAs can distinguish tumor from non-tumor, and are involved in cancer cell proliferation, apoptosis, invasion, and migration both in vitro and in vivo 1722. Furthermore, the altered expression of piRNAs is strongly associated with clinical outcome, highlighting their important role in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the altered expression of piRNAs is strongly associated with clinical outcome, highlighting their important role in cancer. piRNAs may serve as novel diagnostic and prognostic biomarkers, and as effective targets for cancer therapy 1722. piRNAs could repress the mobilization of transposable elements (TEs) and regulate the expression of downstream target genes to maintain genomic integrity via transcriptional or post-transcriptional mechanisms.…”
Section: Introductionmentioning
confidence: 99%